2021
DOI: 10.1111/rda.13972
|View full text |Cite
|
Sign up to set email alerts
|

Induction of reproductive activity and egg production by gonadotropin‐releasing hormone in non‐laying hens

Abstract: The current study was conducted to evaluate the effects of gonadotropin‐releasing hormone (GnRH) analogue (Receptal) injection on reproductive traits of fully mature layers hens (32 weeks) suffered from inactive ovaries. Ninety‐six non‐laying hens (TETRA‐SL brown egg layers), selected from a commercial flock, with similar body weight, were randomly assigned to four groups (n = 24). Hens in the 1st group served as a control. Hens of the 2nd, 3rd and 4th groups were individually intramuscularly injected every 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Lower number of pvalue equates to higher enrichment. E Protein interaction modules of the top 10 marker genes in cluster 0, cluster 3, cluster 12 and cluster 15 and L_C. The high-quality transcriptomes, collectively expressing about 17 k genes, provided strong statistical power for unbiased decompositionof these cell populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower number of pvalue equates to higher enrichment. E Protein interaction modules of the top 10 marker genes in cluster 0, cluster 3, cluster 12 and cluster 15 and L_C. The high-quality transcriptomes, collectively expressing about 17 k genes, provided strong statistical power for unbiased decompositionof these cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of thyroid-stimulating hormone β subunit (TSHB), deiodinase 2 (DIO2), organic anion transporting polypeptides (OATPs) are subsequently enhanced, which modulate gonadotropin-releasing hormone (GnRH) secretion from the hypothalamus [12][13][14]. GnRH regulates the release of gonadotropins, such as luteinizing hormone (LH), follicle-stimulating hormone (FSH), estrogen and progesterone hormones which subsequently arouses egg laying [15].…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of egg laying seems to be regulated by the hypothalamic-pituitary-ovarian ( HPO ) axis ( Gloux, et al, 2019 ), and the particular interconnected hormones or neuropeptides facilitate the secretion of sex hormones from the ovaries, thereby promoting oocyte maturation and ovulation ( Hanafy and Elnesr, 2021 ). Dunn, et al (2004) found that a 4bp indel on the NPY gene approximately 700bp upstream of the transcription start site had a significant dominant effect on AFE in broilers, with heterozygous individuals having earlier AFE.…”
Section: Introductionmentioning
confidence: 99%
“…The main clinical characteristics of salpingitis of laying hens are decreased egg production, no or short maintenance time of peak of laying eggs, poor eggshell quality, increase of thin, soft and sandy shell eggs, which causes great economic losses to the poultry industry. The success of the poultry industry depends mainly on the reproductive status of the birds ( Hanafy and Elnesr, 2021 ; El Sabry et al., 2022 ). So the salpingitis is one of the frequent diseases threatening the healthy development of laying hens farming industry ( Fang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%